Toll Road Development and Environmental Change: A Maqashidi Study at Indralaya – Muara Enim - Muyasaroh; Herlina (Millah: Journal of Religious Studies, 2022)
The Government of Indonesia builds toll roads in many regions of Indonesia, including 119 km of the Indralaya - Muara Enim intersection, to accelerate barrier-free connectivity for the community. This study analyzes the concept of environmental change from the impact of the construction of the toll road on the Indralaya community. This study uses a qualitative approach with an inductive research type. The data were analyzed using NVivo 12 Plus. The results showed that environmental change must be based on the principle of mutual benefit. The construction of toll roads must involve the local community to create conducive conditions. Negative impacts on the environment in the development process must be minimized through dialogue and contributions from the surrounding community. The construction of the Indarala – Muara Enim toll road in general has met the requirements of ushul al khamsah or basic needs of maqashid sharia. However, there is still a lack of anticipation from this implementation project because there are still complaints from the public, which can be read from respondents' responses. Environmental changes related to the construction of toll roads must use a structured and orderly concept. In this case, the concept of environmental change must be bound by the rules and legislation to anticipate and provide solutions to the negative impacts that occur in the form of minimal compensation for land or buildings affected by the project at a reasonable price, dealing with contaminated or polluted air and noise quickly and responsively.